Effectiveness of Palm Sugar and Cinnamon Herbal Tea on Blood Sugar Levels Patients with Type 2 Diabetes Mellitus: An Experimental Study in the Community - Devi Susanti; Arpina Fajarnita; Herlitawati Herlitawati; Taufik Hidayat (Jurnal EduHealth, 2025)
Type 2 Diabetes Mellitus (DM) is a global health problem with increasing prevalence. Controlling blood sugar levels through herbal interventions has become a popular alternative due to its accessibility, relative affordability, and minimal side effects. Palm sugar has a low glycemic index, while cinnamon contains active compounds that can improve insulin sensitivity. The purpose of this study was to determine the effectiveness of palm sugar and cinnamon herbal tea on blood sugar levels in patients with type 2 Diabetes Mellitus. This study used a quasi-experimental design with a pre-post test approach in one treatment group conducted in Babussalam District, Southeast Aceh Regency. A total of 40 respondents diagnosed with type 2 DM were divided into an intervention group (n=20) given palm sugar and cinnamon herbal tea, and a control group (n=20) who only received dietary education. The intervention was given for 14 days at a dose of one glass per day. Fasting blood sugar levels were measured before and after the intervention. Data were analyzed using paired t-tests and independent t-tests. The majority of respondents were aged 45-60 years (65%), female (60%), and had a family history of type 2 diabetes (55%). The intervention group experienced a significant decrease in fasting blood sugar levels of 32.8 mg/dL (from 182.5±21.3 mg/dL to 149.7±18.5 mg/dL; p<0.001), while the control group only experienced a decrease of 6.3 mg/dL (p=0.087). Comparison between the two groups showed a significant difference (p<0.01).